Osteogenic transdifferentiation of vascular smooth muscle cells isolated from spontaneously hypertensive rats and potential menaquinone‐4 inhibiting effect. Issue 11 (1st April 2019) - Mandatori, Domitilla; Pipino, Caterina; Di Tomo, Pamela; Schiavone, Valeria; Ranieri, Antonia; Pantalone, Sara; Di Silvestre, Sara; Di Pietrantonio, Nadia; Ucci, Mariangela; Palmerini, Carola; Failli, Paola; Di Pietro, Natalia; et al.
Abstract: Vascular calcification (VC) is an active and cell‐mediated process that shares many common features with osteogenesis. Knowledge demonstrates that in the presence of risk factors, such as hypertension, vascular smooth muscle cells (vSMCs) lose their contractile phenotype and transdifferentiate into osteoblastic‐like cells, contributing to VC development. Recently, menaquinones (MKs), also known as Vitamin K2 family, has been revealed to play an important role in cardiovascular health by decreasing VC. However, the MKs' effects and mechanisms potentially involved in vSMCs osteoblastic transdifferentiation are still unknown. The aim of this study was to investigate the possible role of menaquinone‐4 (MK‐4), an isoform of MKs family, in the modulation of the vSMCs phenotype. To achieve this, vascular cells from spontaneously hypertensive rats (SHR) were used as an in vitro model of cell vascular dysfunction. vSMCs from Wistar Kyoto normotensive rats were used as control condition. The results showed that MK‐4 preserves the contractile phenotype both in control and SHR‐vSMCs through a γ‐glutamyl carboxylase‐dependent pathway, highlighting its capability to inhibit one of the mechanisms underlying VC process. Therefore, MK‐4 may have an important role in the prevention of vascular dysfunction and atherosclerosis, encouraging further in‐depth studies to confirm its use as a natural food supplement. Abstract : Vascular smooth muscle cells (vSMCs) osteogenic transdifferentiation is one of the key events during vascular calcification process. This study demonstrates that menaquinone‐4 (MK‐4), also known as vitamin K2, is able to inhibit the osteogenic transdifferentiation through the gamma‐glutamyl carboxylase (GGCX)‐dependent pathway in a model of vSMCs isolated from the thoracic aorta of spontaneously hypertensive rats (SHR).